Eksplorasi etnomatematika kue apem dalam tradisi tahlilan di Tulungagung - Azzahro, Sabrina; Saputri, Rizqi Rahmadhani (Maliki Interdisciplinary Journal, 2025)
Kue apem is a traditional food that has a round shape and is white in color. Kue apem is served in several events such as tahlilan events. The tahlilan tradition is a tradition to commemorate death that aims to pray for people who have died. Exploration of the ethnomathematics of kue apem in the tahlilan tradition shows that kue apem is a mandatory dish at every tahlilan event. Kue apem itself has symbolic value as a symbol of determination not to repeat the sins that have been committed. In addition to being a mandatory dish in a tahlilan tradition, kue apem also has a mathematical concept contained therein. Kue apem has a mathematical concept in the form of kue apem shape which has a tube shape that shows geometry material and kue apem has a mathematical concept in the form of comparison in the composition of ingredients. This study aims to explore the ethnomathematics contained in kue apem. The exploration results from this journal explain that kue apem has an ethnomathematics concept from the history and shape of kue apem and has mathematical concepts of geometry and comparison.